PENGEMBANGAN LKPD KIMIA BERBASIS INKUIRI MATERI KIMIA TANAH UNTUK MENINGKATKAN PENGUASAAN KONSEP SISWA SMKN PRETANIAN 2 TUGUMULYO - Yeni Trianah (LP4MK STKIP PGRI Lubuklinggau, 2021)
This development research aims to (1) produce an inquiry-based chemistry worksheet that is appropriate as a student learning medium, (2) to find out the magnitude of the increase in students' conceptual mastery after using inquiry-based worksheets. This research is a development research using the Borg & Gall development model, namely 1) preliminary study, 2) planning, 3) development, 4) limited trial, 5) revision, 6) field test, 7) final product improvement. This research was conducted at SMKN Agriculture 2 Tugumulyo. The feasibility of the Inquiry-Based Chemical LKPD is seen from the score using SBI analysis. The increase in learning outcomes is seen from the value of the Standard Gain pretest and posttest. The results of this study are 1) the inquiry-based chemistry worksheets that were developed are suitable for use as a learning medium for students with an assessment score of 60.5 in the good category. 2) The increase in students' mastery of concepts is 0.48 in the medium category.